Sillan Interpreters in 9th-century East Asian Exchanges - Lung, Rachel (Meta, 2015)
Interpreters are often anonymously and flimsily archived, given their subsidiary role in diplomatic exchanges. These fragmentary records pose problems for in-depth studies on ancient interpreters. Japanese monk Ennin’s (794-864) diary documenting his decade-long (838-847) China sojourn, however, provides a delightful contrast to this evidence limitation. Known for its authentic, detailed, and objective descriptions, it contains thirty-eight references to four Sillan (ancient Korean) interpreters, of whom one was an interpreting clerk affiliated with a prefecture in eastern coastal China. He was also Ennin’s longest-serving interpreter, from 839 through 847, having been documented twenty-three times. This interpreting functionary, Yu Sinǒn, worked in a regional office of a Sillan enclave and assisted visitors from Japan and Silla. His work, apart from language mediation, included liaising, trading, logistics and message go-betweens. As a civil servant, this Sillan interpreter was expected to be law-abiding. Yet in his mediating services for Ennin, he frequently flouted the legal limits. In the process, he was given monetary rewards, although later textual hints suggest that his mediation for the Japanese monks was primarily based on goodwill and friendship. The detailed descriptions in Ennin’s travelogue offer us first-hand information about an interpreting official’s infringements of the Tang Chinese laws. However, was it not exactly his official position, with easy access to institutional networks and legal bureaucracy, which enabled him to work around the loopholes? This case of an interpreter and his patron provides valuable evidence for the development of their initial professional ties and subsequent personal bonding. It also speaks of the arbitrary boundaries between interpreting officials and civilian interpreters in first-millennium East Asian exchanges.